Positive Classification Advantage of Categorizing Emotional Faces in Patients With Major Depressive Disorder - Zhao, Lun; Wang, Xiaoyu; Sun, Gang (Frontiers in Psychology, 2022)
This study investigated whether MDD (major depressive disorder) patients had the deficit of emotional face classification as well as its perceptual mechanism. We found that compared with the control group, the classification speed of emotional faces in MDD patients was slower and the accuracy was lower. In the control group, happy faces were classified faster than sad faces, i.e., positive classification advantage (PCA), which disappeared under the inverted condition. MDD patients exhibited similar PCA to the control group, although the inversion effect of happy and sad expressions was more evident than that of the control group. These data suggest that the dysfunction of categorizing emotional faces in MDD patients could be due to general impairment in decoding facial expressions, reflecting the more common perceptual motion defects in the classification of facial expressions.